Strategic Financial Management for Performance Enhancement and Sustainable Growth - Arda Lintang Marthanda Suherlan (Arthatama: Journal of Business Management and Accounting, 2024)
Strategic financial management is fundamental to corporate success, ensuring performance enhancement and sustainable growth in an evolving business landscape. This study explores the interconnected roles of financial management, operational efficiency, capital structure, risk mitigation, and sustainability in driving business resilience. Effective financial planning and disciplined cost control are essential for maintaining liquidity and profitability. Additionally, optimizing capital structure minimizes financial risks while maximizing firm value. Robust risk management strategies help businesses navigate uncertainties and mitigate potential disruptions. Furthermore, the integration of financial technology and corporate social responsibility contributes to long-term stability and competitive advantage. Firms that embrace adaptive financial strategies can better respond to market fluctuations, regulatory changes, and emerging economic trends. This study offers valuable insights into best practices for achieving financial sustainability and resilience, emphasizing the importance of continuous innovation and strategic decision-making in financial management. Future research should focus on the impact of financial technology on corporate growth and risk management frameworks.